Adjuvant chemotherapy compared with observation in patients with T2aN0 stage IB lung adenocarcinoma - Lee, Po-Hsin; Chiang, Chun-Ju; Tseng, Jeng-Sen; Zheng, Zhe-Rong; Chen, Kun-Chieh; Chu, Cheng-Hsiang; Huang, Yen-Hsiang; Hsu, Kuo-Hsuan; Lee, Wen-Chung; Yang, Tsung-Ying; Liu, Tsang-Wu; Hsia, Jiun-Yi; et al. (Frontiers in Oncology, 2023)
Introduction For patients with T2aN0 stage IB lung adenocarcinoma, benefits of adjuvant chemotherapy remain controversial. Here, we aimed to evaluate such benefits. Methods This retrospective cohort study was conducted on the database of the National Taiwan Cancer Registry. We analyzed patients with T2aN0 stage IB lung adenocarcinoma (re-classified by AJCC 8th edition) diagnosed during the period from January 2011 to December 2017. They were divided into two groups: (1) group 1: tumor <=3 cm with visceral pleural invasion (VPI); (2) group 2: tumor >3 cm, but <=4 cm. Overall survival (OS) and cancer specific survival (CSS) were evaluated. Risk factors for survival were determined. Results A total of 2,100 patients with T2aN0 stage IB lung adenocarcinoma (1,265 in group 1 and 835 in group 2) were enrolled for study. The proportions of patients receiving adjuvant chemotherapy in group 1 and 2 were 39.1% and 68.6%, respectively. Amongst group 1 patients, adjuvant chemotherapy was not an independent risk factor for OS and CSS. Amongst group 2 patients, high-grade histologic findings and receiving sublobar resection were two risk factors for poorer survival. Adjuvant chemotherapy was also associated with an OS (adjusted hazard ratio (aHR), 0.52; 95% confidence interval (CI), 0.38-0.72; P<0.001) and CSS (aHR, 0.54; 95% CI, 0.37-0.78; p=0.001) benefit regardless of the presence or absence of risk factors. Conclusion For patients with T2aN0 stage IB lung adenocarcinoma, adjuvant chemotherapy improved OS and CSS in those with tumors >3 cm, but <=4 cm.For patients with tumors <=3 cm with VPI, adjuvant chemotherapy had no survival benefit.